Platelet interaction with rabbit subendothelium in von Willebrand's disease: altered thrombus formation distinct from defective platelet adhesion. - Turitto, V T (1984)
Blood interaction with the subendothelium of rabbit aorta was investigated in an annular perfusion chamber using patients with von Willebrand's disease, hemophilia, and afibrinogenemia. The vessels were exposed to nonanticoagulated blood for a range of flow conditions (wall shear rates of 650-3,300 s-1) and exposure times (1.5-10 min). The resultant platelet and fibrin interaction was quantified by the use of several morphometric techniques, one of which was developed to measure more precisely the dimensions (height and volume) of platelet thrombi attached to the subendothelium. A major finding was that under flow conditions in which little or no defect in platelet adhesion was observed in von Willebrand's disease, platelet thrombus height and volume in this disorder were significantly reduced as compared with normal controls or patients with hemophilia. Thus, Factor VIII/von Willebrand factor (VIII/VWF) may mediate not only the adhesion of platelets to subendothelium but also platelet-platelet attachments necessary for normal thrombus development. The level of Factor VIII:coagulant activity (VIII: C) was also observed to influence the resultant thrombus height and volume deposited on subendothelium, presumably through the generation of thrombin or some other procoagulant factor preceding fibrin formation, since normal values of thrombus dimensions were always observed in a patient with a fibrinogen deficiency. The influence of VIII:C became greater as shear rate was reduced, whereas as shear rate was increased, VIII/VWF was more dominant in determining the resultant platelet deposition on subendothelium. Thus, the deficiencies of VIII:C and VIII/VWF in hemophilia and von Willebrand's disease can lead to various abnormalities in platelet and fibrin association with subendothelium. The importance of a particular deficiency will depend strongly on the local blood flow conditions.